The Influence of Sharia Supervisory Board, Firm Size, and Firm Age on the Profitability of Islamic Commercial Banks in Indonesia During the 2018–2023 Period - Prasetyo Widodo, Annis Azizah; Mochamad Edman Syarief; Muhammad Syaiful Nurasman (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
This study aims to analyze the influence of the Sharia Supervisory Board (SSB), firm size, and firm age on the profitability of Islamic Commercial Banks in Indonesia during the 2018–2023 period. The research employs a quantitative descriptive approach using panel data. The population includes all Islamic Commercial Banks registered with the Financial Services Authority (OJK), with a sample of 11 banks selected based on specific criteria. The data used are secondary data obtained from the annual reports of these banks. Panel data regression analysis was applied to examine the relationship between the independent variables (SSB, firm size, and firm age) and the dependent variable (profitability, measured by Return on Equity or ROE). The findings reveal that, individually, the number of SSB members, frequency of SSB meetings, expertise in economics and accounting, dual positions, and firm size do not have a significant effect on ROE. Only firm age was found to have a significant impact. The adjusted R-squared value of 2.2171% suggests that other variables outside the model play a more dominant role in explaining profitability. These findings are expected to contribute to strengthening governance and improving the performance of Islamic banking institutions. Keywords: Sharia Supervisory Board, Firm Size, Firm Age, Profitability, Islamic Commercial Banks.